2011
DOI: 10.1016/s0960-9776(11)70311-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant systemic treatment for individual patients with triple negative breast cancer

Abstract: Chemotherapy is the only evidence based adjuvant systemic treatment option in triple negative breast cancer (TNBC). Despite emerging results for targeted biological therapies for this subpopulation, lack of robust results does not currently support their use beyond the confines of a clinical trial. Conventional systemic chemotherapy remains the standard of care and is curative in a minority of patients. There is no defined standard chemotherapy and there is currently no robust, prospective, randomized data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…However, more than one-half of TNBCs do not respond to chemotherapy. 31 Predictably, patients who do not obtain a complete pathologic response have a high likelihood of disease relapse, frequent distant metastases, and a poorer prognosis compared with patients who have hormonal receptor-positive breast cancer. As compared with patients who have non-TNBCs, patients with TNBCs are younger at disease onset (,50 years) with a higher tumor grade at diagnosis and a higher rate of developing metastatic disease.…”
Section: Distinguishing Between Papillary Lesionsmentioning
confidence: 99%
“…However, more than one-half of TNBCs do not respond to chemotherapy. 31 Predictably, patients who do not obtain a complete pathologic response have a high likelihood of disease relapse, frequent distant metastases, and a poorer prognosis compared with patients who have hormonal receptor-positive breast cancer. As compared with patients who have non-TNBCs, patients with TNBCs are younger at disease onset (,50 years) with a higher tumor grade at diagnosis and a higher rate of developing metastatic disease.…”
Section: Distinguishing Between Papillary Lesionsmentioning
confidence: 99%
“…Studies on neoadjuvant chemotherapy have shown that TNBC patients with pathological complete response (pCR) to treatment correlate with good clinical outcomes, with rates similar to non-TNBC patients. However, most TNBC patients (63%) have residual disease after treatment, showing a peak risk of relapse at around three years posttreatment, as well as an increased mortality rate [74%] [Carey et al, 2007;Dent et al, 2007;Cheang et al, 2008;Liedtke et al, 2008;Dent et al, 2009;Oakman et al, 2011;Andre and Zielinski 2012;Yu et al, 2013]. Although there are two TNBC patient groups: chemotherapysensitive and chemoresistant, the mechanism of this differing treatment response is unknown and so there is a clear need to resolve these differences and/or to identify specific targets as the basis for future therapies.…”
Section: ;mentioning
confidence: 99%
“…8 Unfortunately, standard chemotherapy compounds are rarely effective and TNBC tumors often lead to incurable metastatic disease. 7,9,10 …”
Section: Introductionmentioning
confidence: 99%